2018
DOI: 10.3324/haematol.2018.192468
|View full text |Cite
|
Sign up to set email alerts
|

Physician uncertainty aversion impacts medical decision making for older patients with acute myeloid leukemia: results of a national survey

Abstract: Elderly patients with acute myeloid leukemia can be treated with intensive chemotherapy, low-intensity therapy such as low-dose aracytine or hypomethylating agents, or best supportive care. The choice between these treatments is a function of many patient-related and disease-related factors. We investigated how physicians’ behavioral characteristics affect medical decision-making between intensive and non-intensive therapy in this setting. A nationwide cross-sectional online survey of hematologists collected d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 48 publications
0
19
1
3
Order By: Relevance
“…Furthermore, the proportion of patients age < 75 years who had none, one, two or more co‐morbidities was unclear in the venetoclax and ivosidenib studies, as was the effect of the number of co‐morbidities, or their type, on TRM, survival, or toxicity. Bories et al have demonstrated assessment of “unfitness” is often subjective; given the same scenarios physicians more willing to accept risk in their own lives were more likely to recommend more intense induction 44 . Eight of 24 patients who did not respond to venetoclax + HMA went on to receive intensive “salvage” therapy, suggesting they may have been fit to receive such therapy at initial diagnosis, although median survival after intense therapy was only 2‐3 months 45 .…”
Section: Treatmentmentioning
confidence: 99%
“…Furthermore, the proportion of patients age < 75 years who had none, one, two or more co‐morbidities was unclear in the venetoclax and ivosidenib studies, as was the effect of the number of co‐morbidities, or their type, on TRM, survival, or toxicity. Bories et al have demonstrated assessment of “unfitness” is often subjective; given the same scenarios physicians more willing to accept risk in their own lives were more likely to recommend more intense induction 44 . Eight of 24 patients who did not respond to venetoclax + HMA went on to receive intensive “salvage” therapy, suggesting they may have been fit to receive such therapy at initial diagnosis, although median survival after intense therapy was only 2‐3 months 45 .…”
Section: Treatmentmentioning
confidence: 99%
“…Validated therapeutic options are currently limited. Patient selection for intensive versus low-intensity therapy remains controversial [3,4] and inter-physician practice variations are frequent, which underscores the uncertainty on the optimal strategy for any elderly AML patient [5].…”
Section: Introductionmentioning
confidence: 99%
“… Bernardes et al, 2013 [ 55 ] Whether physician sex moderates the effects of patient (distressed) pain behaviours and diagnostic evidence of pathology on treatment prescriptions and referrals; explore the mediating role of pain credibility judgments and psychological attributions on these effects Portugal Primary care Physician Referral, prescription, assessment Gender Physician sex, clinical cues (evidence of pathology, distress) Chronic lower back pain Confirming the hypothesis, physician sex moderates the influence of clinical cues on pain management practices: evidence of pathology had a larger effect on male than on female physicians’ referrals to psychology/psychiatry. Bories et al, 2018 [ 56 ] To test the hypothesis that physician uncertainty aversion impacts medical decision making for older patients with acute myeloid leukaemia France Acute Physician Prescription Age (note clinically relevant) Physician demographic, occupational, behavioural characteristics Acute myeloid leukaemia Physician attitudes to risk influenced chemotherapy decisions for older patients. Physicians opting for intensive chemotherapy (IC) had higher aversion to uncertainty and treated fewer patients annually, than the low IC group but were similar in age, hierarchical status or years of experience.…”
Section: Resultsmentioning
confidence: 99%